High-School Teachers’ Beliefs about Effort and Their Attitudes toward Struggling and Smart Students in a Confucian Society - Chen, Shun-Wen; Fwu, Bih-Jen; Wei, Chih-Fen; Wang, Hsiou-Huai (Frontiers in Psychology, 2016)
Previous studies conducted in Western societies showed that instructors’ beliefs about intellectual ability affected their attitudes toward students. However, in many East Asian societies influenced by Confucian culture, teachers not only hold beliefs of ability but also two kinds of beliefs about effort: obligation-oriented belief (i.e., believing that effort-making is a student’s role obligation) and improvement-oriented belief (i.e., believing that effort can conquer the limitations of one’s ability). This study aimed to investigate the relationships between teachers’ effort beliefs and their attitudes toward favoritism, praise, and expectations toward struggling and smart students. The participants were 151 Taiwanese high-school teachers. Results of Structure Equation Modeling showed that (1) teachers’ obligation-oriented belief about effort was positively correlated with their favoritism, praise, short-term and long-term expectations of struggling students, but negatively correlated with their favoritism and praise of smart students, (2) teachers’ improvement-orientated belief about effort was negatively correlated with their short-term expectation of smart students and favoritism of struggling students, but positively correlated with their praise of smart students, and (3) the entity theory of intelligence was negatively correlated with favoritism and praise of struggling students, but positively correlated with favoritism of smart students. The theoretical and cultural implications are discussed.